Efektivitas Konseling DM dalam Meningkatkan Kepatuhan dan Pengendalian Gula Darah pada Diabetes Melitus Tipe 2 - Sucipto, Adi (Universitas Muhammadiyah Yogyakarta, 2014)
Background. Diabetes mellitus (DM) is a chronic metabolic disease characterized by elevated levels of glucose in the blood. Poor adherence to treatment of patients with type 2 diabetes causes uncontrolled blood glucose soincreasing the risk of various complications. One major factor is the failure of a treatment noncompliance to therapy is planned. Counseling is one way to improve the knowledge , attitudes and patient compliance.Objective. This study aimed to evaluate the eff ectiveness of counseling in improving compliance and diabetes control blood sugar in patients with type 2 diabetes.Research Design. This study is an experimental study with a quasi experiment design with pre and post test control group design prospectively performed in Dr Soeradji Tirtonegoro Klaten from March to December 2014. Thesample consisted of 44 respondents, with 22 intervention and 22 control group. The measurement results were analyzed using the paired t test to test blood sugar levels 2 hours post- prandial ( GDPP ) and Mac Nemar test for levels of patient compliance.Results. The analysis showed there are signifi cant diff erence before and after adherence counseling in the intervention group (p diet =0.001; p control = 0.002; p = 0.000 pill count; GDPP p = 0.000 ) and have not signifi cant diff erence in the exercise group (p value =0.549)Conclusions. This study indicates that counseling is very eff ective in improvingdiabetes diet compliance, control and pill count and post prandial blood sugar complianceb(GDPP) and are not eff ective in improvingbexercise compliance of patients .Keywords: counseling, compliance, diabetes mellitus